Enhancing programming language learning with 3D game-based programming for MSU students: codadventure / Abdullah Adib Aditia Wirawan and Nur Suhana Mohd Redzo - Aditia Wirawan, Abdullah Adib; Mohd Redzo, Nur Suhana (2024)
This study focuses on innovative approaches to enhance the learning experiences of programming languages, focusing on developing 3D game-based programming for students at Management & Science University (MSU). The study thoroughly examines the difficulties encountered in conventional programming education and emphasizes the potential advantages of utilizing immersive gamified techniques. The students face challenges while learning programming languages and memorizing programming concepts. The research emphasizes individuals' syntax, debugging, and algorithmic writing difficulties. Conventional face-to-face learning methods result in a relatively low average score of 3.50 in understanding syntax. The instructor's methodology also guides the students in teaching and learning programming language using the Logic Learning method in the game. The project's objective is to reduce the common difficulties MSU students face in learning programming languages. This was achieved by creating a 3D game-based programming platform called Codadventure. The game's development implemented Unity3D to create a platform that enhances the memorization of programming concepts. Furthermore, the research provides educators with efficient techniques for improving students' learning in acquiring programming languages using the Logic Learning method integrated into the game. The project uses the Game Development Life Cycle (GDLC) to facilitate methodical development. The approach involves doing a Pearson correlation coefficient heatmap analysis, specifically examining factors such as Enhancement, Gameplay, Familiarity, and Engagement. Utilizing data analysis and student feedback allows for significant insights into the effects of the 3D game-based method on the adoption of programming languages. In the future, the project has the potential to include an adaptive learning path that customizes the educational experience on the individual student's progress, abilities, and areas that need to be developed.